Temperature sensitivity of a fabricated fiber bragg grating - Someraa Saleh Ali, 1983-; Jalil Ali, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010